Identifikasi Senyawa Kimia pada Tanaman Pulai (Alstonia scholaris) Sebagai Pestisida Nabati untuk Pengendali Hama - Syarifuddin, Rifni Nikmat; AR, Trisnawaty; Nurwidah, Andi (Journal Galung Tropika, 2021)
<span style="font-size: 11.0pt; font-family: ’Times New Roman’,serif; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US">Currently, farmers still rely heavily on chemicals in controlling plant-disturbing organisms. This is supported by increasing the number of pesticides registered and circulating in the market from year to year. Based on the principle of IPM (Integrated Pest Management), pesticides are the last alternative if other control methods cannot reduce the pest population. However, the farmers in Compong Village, Pitu Riase District, Sidrap Regency, are still using one of the local wisdom to control pest populations. The pest control utilizes plant parts, one of which is the pulai plant (Alstonia scholaris). However, the use of pulai plant extracts has not been optimal because information on the types of chemical compounds and their functions is not widely known. This study aims to determine the types of chemical compounds in the leaves and stems of pulai plants that can be used as vegetable pesticides. The research was started by making a fine powder from the leaves and stems, after which the extraction was carried out by the maceration technique with methanol for 4×24 hours. The extract was then subjected to a phytochemical test. The test results showed that the leaf extract of the pulai plant contained saponins, flavonoids, and alkaloids. While the stem extract only contains saponins and alkaloids. This result shows that the pulai plant has the potential to be used as an environmentally friendly vegetable pesticide.<span style="font-size: 11.0pt; font-family: ’Times New Roman’,serif; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US">Currently, farmers still rely heavily on chemicals in controlling plant-disturbing organisms. This is supported by increasing the number of pesticides registered and circulating in the market from year to year. Based on the principle of IPM (Integrated Pest Management), pesticides are the last alternative if other control methods cannot reduce the pest population. However, the farmers in Compong Village, Pitu Riase District, Sidrap Regency, are still using one of the local wisdom to control pest populations. The pest control utilizes plant parts, one of which is the pulai plant (Alstonia scholaris). However, the use of pulai plant extracts has not been optimal because information on the types of chemical compounds and their functions is not widely known. This study aims to determine the types of chemical compounds in the leaves and stems of pulai plants that can be used as vegetable pesticides. The research was started by making a fine powder from the leaves and stems, after which the extraction was carried out by maceration technique with methanol for 4×24 hours. The extract was then subjected to a phytochemical test. The test results showed that the leaf extract of the pulai plant contained saponins, flavonoids, and alkaloids. While the stem extract only contains saponins and alkaloids. This result shows that the pulai plant has the potential to be used as an environmentally friendly vegetable pesticide.